Effects of Dumping Pig Manure into a Lake –The Simpsons Movie - Chagan, Sonal (Journal of Interdisciplinary Science Topics, 2017)
This paper examines the environmental effects of disposing a silo of pig manure into a body of water the size of a lake. It was calculated that the concentration of manure once dispersed in the lake would be 1.3 g m-3. From the qualitative research it was found that eutrophication would occur and lead to effects that would cause damage to the organisms of the lake. Observable changes such as colour change of the water would also take longer to occur than suggested in the movie. This also applies to the potential genetic effects which would only affect aquatic organisms such as fish, and would take at least 1 month to become observable.